Research on the Relationship Between Vestibular Migraine With/Without Cognitive Impairment and Brainstem Auditory Evoked Potential - Zhang, Lei; Chen, Qi-hui; Lin, Jing-han; Zhou, Chang; Pan, Yong-hui (Frontiers in Neurology, 2020)
Background Vestibular migraine (VM) is the most common cause of spontaneous vertigo which no specific physical examination and laboratory examination, and is an under-recognized entity with substantial burden for the individual and society. In this study, by observing the brainstem auditory evoked potential (BAEP) and cognitive function of VM patients, the possible laboratory diagnostic indicators of VM and the influence of disease on cognitive function were discussed. Method The study included 78 VM patients, 76 migraine patients and 79 healthy individuals. The age, gender, and other clinical history of the three groups matched. All participants underwent BAEP examinations, in which patients in the migraine group and outpatients of the VM group were in the interictal period, and inpatients in the VM group were examined during episodes, while all patients were tested for the Addenbrooke's cognitive examination-revised (ACE-R) scale were in the interictal period. The differences in BAEP and ACE-R scores between the three groups of members and their relationship with the clinical features of VM patients were analyzed. Result The peak latency of I, III and V wave in the BAEP of the VM group was longer than that of the migraine group and the control group (p<0.05). The peak latency of V wave in the BAEP of the migraine group was longer than that of the control group (p<0.05). The ACE-R of VM group scored lower than the migraine group in terms of language fluency and language (p<0.05), and lower than the control group in terms of total score, language fluency, language and visuospatial (p <0.05); and the ACE-R of the migraine group scored lower than the control group in the total score and visuospatial (p<0.05). Conclusion Migraine patients have brainstem dysfunction，and VM patients have more severe brainstem dysfunction than migraine patients, suggesting that VM patients have both central nervous system damage and peripheral nerve damage. Migraine patients have cognitive impairment, while cognitive impairment in VM patients is more severe than in migraine patients.